PERLINDUNGAN KONSUMEN DALAM PERBANKAN - Joni Saputra (LPPM Universitas Islam Indragiri, 2025)
This article discusses consumer protection in banking. As the times evolve and the number of financial service providers increases, it is necessary to improve protection for consumers who collaborate with these banks. Among the consumer protection provisions in Indonesia, specifically in banking, is the Consumer Protection Law, stipulated in Law Number 8 of 1999. Furthermore, banking regulations also include consumer protection, stipulated in Bank Indonesia Regulation Number 22/20/PBI/2020. Furthermore, the Financial Services Authority (OJK) also has regulations that protect consumers, stipulated in Financial Services Authority Regulation of the Republic of Indonesia Number 22 of 2023.